2018
DOI: 10.1021/acs.est.7b06218
|View full text |Cite
|
Sign up to set email alerts
|

Concentration Dependent Effects of Bovine Serum Albumin on Graphene Oxide Colloidal Stability in Aquatic Environment

Abstract: The impacts of a model globular protein (bovine serum albumin, BSA) on aggregation kinetics of graphene oxide (GO) in aquatic environment were investigated through time-resolved dynamic light scattering at pH 5.5. Aggregation kinetics of GO without BSA as a function of electrolyte concentrations (NaCl, MgCl, and CaCl) followed the traditional Derjaguin-Landau-Verwey-Overbeek (DLVO) theory, and the critical coagulation concentration (CCC) was 190, 5.41, and 1.61 mM, respectively. As BSA was present, it affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 55 publications
1
58
0
Order By: Relevance
“…Non-covalent interactions between proteins and GO have a critical influence on the nanomaterial dispersion stability in aqueous medium and lead to the coronation [ 53 ]. In addition, GO can absorb biomolecules by different mechanisms such as hydrogen bonding, hydrophobic interaction, π-π stacking, electrostatic and van der Waals interactions [ 9 , 54 ]. Sun et al (2018) demonstrated that BSA affects the GO colloidal stability in a nonlinear relationship with the BSA concentration, suggesting an integrated result of compressing electric double layers and steric repulsion induced by the interactions of BSA and GO [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-covalent interactions between proteins and GO have a critical influence on the nanomaterial dispersion stability in aqueous medium and lead to the coronation [ 53 ]. In addition, GO can absorb biomolecules by different mechanisms such as hydrogen bonding, hydrophobic interaction, π-π stacking, electrostatic and van der Waals interactions [ 9 , 54 ]. Sun et al (2018) demonstrated that BSA affects the GO colloidal stability in a nonlinear relationship with the BSA concentration, suggesting an integrated result of compressing electric double layers and steric repulsion induced by the interactions of BSA and GO [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, GO can absorb biomolecules by different mechanisms such as hydrogen bonding, hydrophobic interaction, π-π stacking, electrostatic and van der Waals interactions [ 9 , 54 ]. Sun et al (2018) demonstrated that BSA affects the GO colloidal stability in a nonlinear relationship with the BSA concentration, suggesting an integrated result of compressing electric double layers and steric repulsion induced by the interactions of BSA and GO [ 9 ]. More recently, it was also demonstrated that GO materials displaying different lateral sizes and functional groups exhibited different interactions with BSA in aqueous medium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 In the case of proteins, a 'protein corona' 27 is formed which may signicantly affect not only the protein structure and function but also the biological characteristics of GO. [28][29][30] The formation of the protein corona on the surface affects the fate of the designed nanomaterials. 31,32 Thus, a comprehensive study of the effect of surface modications of GO on its interaction with proteins is required for understanding and improving its biomedical efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…12 GO-protein interactions have been studied, using techniques such as Circular Dichroism (CD), uorescence, UV-Vis spectroscopy, and Fourier transform Infra-Red spectroscopy (FTIR). 30,33,34 Using NMR spectroscopy, information about the dynamics of the protein and its individual residues can be obtained across a varying range of time scales. 35 This feature renders NMR a powerful spectroscopic technique for probing structural and dynamic perturbations in the protein backbone upon its interaction with GO.…”
Section: Introductionmentioning
confidence: 99%